Mechanoregulation of bone formation : from embryogenesis to evolution - Nowlan, Niamh C. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2007)
In summary the author's thesis is that biophysical stimuli mechanoregulate ossification events through the action of mechanosensitive genes, where mechanoregulation is an ontogenetic process which has evolved. The author proposes to conduct the investigation using a systems approach, where biological and computational methods are integrated to investigate and corroborate testable hypotheses. [page 11-12]
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin